Curriculum and Context: Trends in Interventions With Transition-Age Students With Severe Disabilities. (November 2018) - Dymond, Stacy K.; Butler, Anne M.; Hopkins, Shari L.; Patton, Kimberly A.
The purpose of this systematic literature review was to determine trends in the curricular focus and instructional context of intervention research conducted with transition-age students with severe disabilities between 1975 and 2014. A total of 138 studies met inclusion criteria. Across the last three decades, interventions focused on functional skills declined while academic interventions increased. The most frequently used instructional contexts were special education classrooms, simulated activities, mass trials, and either a researcher or nonresearcher as the instructor. Differences in instructional context were present according to curricular focus. Findings suggest the need for interventions that span the breadth of curriculum promoted in the literature with specific emphasis on increasing interventions in areas predictive of positive post-school outcomes. Interventions are also needed that reflect instructional contexts that align more strongly with contexts valued within the field of severe disabilities.